Historiografi Indonesiasentris: problematika dan tantangan - Moch. Dimas Galuh Mahardika; Danan Tricahyono; Erisya Pebrianti Pratiwi; Fahmi Nur Ramadhan (Historiography: Journal of Indonesian History and Education, 2021)
The historical journey of the Indonesian nation needs to be written in its entirety that accommodates various perspectives in order to instill national identity. De-colonization is an attempt to dismantle something colonial, and accentuate something more national or at least 'different' from the colonial. In doing this work there are several problems and challenges that must be faced in order to be able to formulate a complete narrative of Indonesian history by pivoting to nationality. Various efforts have been made to formulate this goal such as, for example, Semniar Sedjarah Nasional 1957 which is considered as the initial milestone of Indonesian historiography. The ideas that appear in the forum are a form of seriousness in formulating Indonesian historiography. Some internal problems post-independence also coloring the pattern of Indonesian historiography.Perjalanan sejarah bangsa Indonesia perlu ditulis secara utuh yang mengakomodir berbagai perspektif dalam rangka menanamkan identitas nasional. De-kolonisasi merupakan suatu usaha untuk membongkar sesuatu yang kolonial, dan menonjolkan sesuatu yang lebih bersifat nasional atau paling tidak ‘berbeda’ dari yang kolonial. Di dalam melakukan pekerjaan ini terdapat beberapa problem dan tantangan yang harus dihadapi untuk dapat merumuskan narasi sejarah Indonesia yang utuh dengan berporos pada nasionalitas. Berbagai usaha telah dilakukan untuk merumuskan tujuan ini seperti misalnya, Seminar Sedjarah Nasional 1957 yang dianggap sebagai tonggak awal historiografi Indonesia. Berbagai gagasan yang muncul dalam forum tersebut merupakan bentuk keseriusan dalam merumuskan historiografi Indonesia. Beberapa problem internal pasca kemerdekaan turut mewarnai corak historiografi Indonesia.